Analisis Kadar Air Perlapisan Tanah Di Lahan Gambut Untuk Menentukan Fire Danger Rating System (FDRS) - Muhamad Azizi; Ari Sandhyavitri; Muhamad Yusa (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Peat is organic soil, but that does not mean organic soil is peat soil. Peatlands in Indonesia are 14.9 million hectares, covering around 50% of the world's tropical peat. Riau Province which has the largest area of peatlands in Indonesia is 55.3%. Unproductive peatlands in Indonesia are reported to be 4.2 million hectares. Under natural conditions, peat is a type of water-saturated soil that can store water up to 5 to 15 times its weight. This research was conducted in the village of Tanjung Leban using peat soil water content of each layer. Results Peat soil moisture content is used to determine the parameters of the Fire Danger Rating System (FDRS) water content. The analysis was conducted using primary data in the form of soil sampling and laboratory testing of soil mechanics. The results of this analysis obtained the value of the average water content of each layer. The average value of layer moisture content is different from the first layer of litter moisture content of 65.39%, the value of moisture content of the second layer of organic soil is 71.22% and the value of moisture content of the third layer of solid soil is 71.04%.Keywords: peat land, Fire Danger Rating System, water content